Role of integrity system, internal control system and leadership practices on the accountability practices in the public sectors of Malaysia - Alam, Md Mahmudul; Said, Jamaliah; Abd Aziz, Mohamad Azizal (Emerald Group Publishing Limited, 2018)
Purpose – This study aims to assess the status of current practices of accountability and its relationship with the practices of integrity system, internal control system and leadership qualities in the public sector of Malaysia. Design/methodology/approach – This study collected primary data from 109 departments and agencies under 24 federal ministries in Malaysia. The data were analysed under descriptive statistics, ordinal regression and structural equation modelling (SEM). Several diagnostic tests were conducted to check the validity and reliability of data and models, such as Cronbach alpha test, Kaiser–Meyer–Olkin test, Shapiro–Wilk test, internal consistency reliability, indicator reliability, convergent validity and discriminant validity. Findings – The regression and SEM results show that the practices of integrity system and leadership quality had statistically significant positive relationship, but the practice of internal control system showed mixed relationship with the practices of accountability.Practical implications – The findings of the study will help the policymakers to ensure better accountability in the public sector in Malaysia and other countries. Originality/value – This is an original study based on primary data to examine the current practices of accountability and its relationship with the practices of integrity system, internal control system and leadership qualities in the public sector of Malaysia